2014
DOI: 10.3171/2014.7.peds14326
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric hydrocephalus: systematic literature review and evidence-based guidelines. Part 6: Preoperative antibiotics for shunt surgery in children with hydrocephalus: a systematic review and meta-analysis

Abstract: Object The objective of this systematic review and meta-analysis was twofold: to answer the question “What is the evidence for the effectiveness of prophylactic intravenous antibiotics for infection prevention in shunt surgery?” and to make treatment recommendations based on the available evidence. Methods The US National Library of Medicine PubMed/MEDLINE database and the Cochrane Database of Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 43 publications
(49 reference statements)
0
19
0
2
Order By: Relevance
“…Many efforts have been taken to reduce the shunt infection rate. Preoperative intravenous (iv) prophylactic antibiotics are administered routinely and this is a mainstay of prevention [ 10 ]. Many different measures appear to contribute to reducing the shunt infection rate, although evidence for each separate measure is minimal or nonexistent [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been taken to reduce the shunt infection rate. Preoperative intravenous (iv) prophylactic antibiotics are administered routinely and this is a mainstay of prevention [ 10 ]. Many different measures appear to contribute to reducing the shunt infection rate, although evidence for each separate measure is minimal or nonexistent [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important actions shown to reduce shunt infections is perioperative prophylactic antibiotics, with the literature supporting their use in all patients undergoing a shunt insertion 2,24 . A systematic review and meta-analysis by Ratilal et al demonstrated that antibiotic prophylaxis can significantly decrease the rate of shunt infection (OR 0.51, 95% CI 0.36-0.73) 25 .…”
Section: Discussionmentioning
confidence: 99%
“…El uso de antibiótico profiláctico sistémico es controversial; sin embargo, la evidencia actual halla un efecto benéfico de su administración con la reducción de las tasas de infección postoperatoria, que varía desde un 20 % hasta un 50 % (43) . Igualmente, sugiere la fuga de LCR como el principal factor de riesgo para la infección, por lo que si persiste por más de 7 días debería considerarse el manejo quirúrgico (31,(44)(45)(46)(47)(48)(49)(50)(51) . En intervenciones quirúrgicas como el drenaje ventricular externo se requiere ampliar la evidencia, especialmente en sí es útil la administración continúa hasta el retiro del catéter (31,49) .…”
Section: Antibióticos Sistémicos Profilácticosunclassified
“…Los regímenes de antibióticos usados en los diferentes estudios no son homogéneos. Dentro de estos, se incluyen el uso de vancomicina, oxacilina, clindamicina, cefazolina, trimetoprim sulfametoxazol, ampicilina y cefalosporinas de tercera generación, los cuales cumplen fundamentalmente con el cubrimiento de microorganismos grampositivos, teniendo en cuenta que el principal agente involucrado es el Staphylococcus spp (31,(44)(45)(46)(47)(48)(49)(50)(51)(52)53) . Algunos estudios han favorecido el uso de vancomicina, especialmente en contextos de alta prevalencia de SAMR, pero otros no han encontrado diferencias entre esquemas (53,54,55) .…”
Section: Antibióticos Sistémicos Profilácticosunclassified